2019
DOI: 10.4062/biomolther.2019.076
|View full text |Cite
|
Sign up to set email alerts
|

Spinosin Attenuates Alzheimer’s Disease-Associated Synaptic Dysfunction via Regulation of Plasmin Activity

Abstract: Hippocampal synaptic dysfunction is a hallmark of Alzheimer's disease (AD). Many agents regulating hippocampal synaptic plasticity show an ameliorative effect on AD pathology, making them potential candidates for AD therapy. In the present study, we investigated spinosin as a regulating agent of synaptic plasticity in AD. Spinosin attenuated amyloid β (Aβ)-induced long-term potentiation (LTP) impairment, and improved plasmin activity and protein level in the hippocampi of 5XFAD mice, a transgenic AD mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Moreover, previous studies have identi ed the potential biomedical function of Spinosin. It has been found that Spinosin inhibits Alzheimer's diseaserelated synaptic disorder by regulating plasmin activity (28). Spinosin is able to activate Nrf2/HO-1 signaling to inhibit the aggregation and production of Aβ 1-42 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have identi ed the potential biomedical function of Spinosin. It has been found that Spinosin inhibits Alzheimer's diseaserelated synaptic disorder by regulating plasmin activity (28). Spinosin is able to activate Nrf2/HO-1 signaling to inhibit the aggregation and production of Aβ 1-42 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Another in vitro study using Neuro-2a cells (N2a/WT) and N2a/APP695 cells showed that spinosyn markedly reduced Aβ1-42 production by activating the Nrf2/HO-1 pathway [119]. In addition, spinosin might be beneficial to treat learning and memory deficits through the regulation of oxidative stress, inflammatory processes, apoptotic programs, and plasmin activity [120][121][122].…”
Section: Moas Of Ingredientsmentioning
confidence: 99%
“…In the neocortex of AD patients, the levels of plasminogen (pro-type of plasmin) and plasmin were lower than healthy controls [ 35 ]. Cai et al reported that AD model mice showed a lower plasmin level in the hippocampus [ 36 ]. They also found that a treatment of spinosyn, a flavonoid isolated from Zizyphus jujuba var spinosa seeds, increased expression and activity of hippocampal plasmin and synaptic plasticity in AD model mice.…”
Section: Bdnf Signaling In Admentioning
confidence: 99%